Effects of ultrasonic assistance on microhole drilling based on Nd:YAG laser trepanning. (October 2018) - Shi, Chunhui; Ren, Naifei; Wang, Houxiao; Xia, Kaibo; Wang, Liang
Highlights: Higher ultrasonic power was more beneficial to laser trepanning quality. Ultrasonic assistance was not helpful to reduce oxidation during laser drilling. Ultrasonic assistance did not alter elemental compositions around drilled hole greatly. Abstract: The ultrasonic vibration was introduced to assist the Nd:YAG laser trepan drilling for improving drilling quality/performance. Effects of ultrasonic power and pulse energy on geometrical and/or metallurgical quality were deciphered for the ultrasonic-assisted Nd:YAG laser trepanning. The energy dispersive spectroscopy analysis was also carried out to reveal the influence of ultrasonic vibration on the elemental compositions of the areas surrounding the drilled microhole entrance. It was shown that the axial ultrasonic vibration coupled into the Nd:YAG laser trepanning process could effectively improve the hole entrance profile/morphology with less metallurgical defects such as microcracks. Moreover, relatively high ultrasonic power was more beneficial to the improvement of laser trepan drilling quality in terms of smaller hole taper angle, thinner recast layer, and less cracks, etc. However, the oxidation of the microhole sidewall could not be effectively improved by using the ultrasonic assistance.